Architecture et croissance des plantes - De Reffye , Philippe; Jaeger , Marc; Barthélémy , Daniel; Houllier , François (éditions Quae, 2016)
This book, in epub format, is the result of 40 years of research on modeling the development and growth of plants. The authors reveal, step by step, the process leading up to the creation of the GreenLab model and the conditions under which it can now be applied.